Nursing care technologies in intensive care units in the context of surgical site infection - Madureira, Arliane Silva (2023)
Objective: to explain the care technologies used by intensive care nurses in the prevention of SSI and in the treatment of infected surgical wounds.  Method: integrative literature review with exploratory descriptive approach and qualitative nature. The descriptors "Health Technologies", Nursing Care Technologies", "Nursing", "Intensive Care Nurse" "Intensive Care Unit", "Surgical Site Infection", "Infected Surgical Wound" and "Surgical Wound Infection", were explored in virtual databases. From the data analysis, two categories were created to perform the thematic analysis. Results: After the analysis, twelve articles were selected. The relevance of the safe surgery checklist, classified as light health technology – hard, was emphasized, being attentive by nursing professionals, in order to prevent SAIs. The study presented data corroborating the reduction in the number of occurrences in view of the observance of the surgical safety checklist, thus verifying the preventive efficiency of this technology. Conclusion: we highlight the need for research focused on the role of intensive care nurses in the use of health care technologies classified as harsh, together with more reliable research methodologies.